1979
DOI: 10.1007/bf01407678
|View full text |Cite
|
Sign up to set email alerts
|

The effect of decerebrate rigidity on the intracranial pressure

Abstract: The mechanical effect of acute decerebrate rigidity upon the ICP and the mechanisms underlying the relationship between them have been investigated with experiments performed on 26 cats. It has been shown that: a) Extreme rigidity of the peripheral musculature with or without partial activation of the trunkal muscles produces no change in ICP, b) the simultaneous elevation of the intra-thoracic and intra-abdominal pressures is the factor primarily operative in raising and maintaining the elevated ICP, c) when … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

1983
1983
1989
1989

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 81 publications
0
1
0
1
Order By: Relevance
“…Posturing was precipitated by flushing the atdal line. While it has been thought that decerebrate rigidity increased pressure, Tsementzis et al (1979) concluded from their study that ICP is raised only when intrathoracic (ITP) and intraabdominal (IAP) pressures are increased and these are not always increased by decerebrate posturing. It is difficult, however, to determine if ITP and IAP will be increased; hence, caution should be used to reduce stimulation which could initiate decerebrate rigidity.…”
Section: Discussionmentioning
confidence: 98%
“…Posturing was precipitated by flushing the atdal line. While it has been thought that decerebrate rigidity increased pressure, Tsementzis et al (1979) concluded from their study that ICP is raised only when intrathoracic (ITP) and intraabdominal (IAP) pressures are increased and these are not always increased by decerebrate posturing. It is difficult, however, to determine if ITP and IAP will be increased; hence, caution should be used to reduce stimulation which could initiate decerebrate rigidity.…”
Section: Discussionmentioning
confidence: 98%
“…Da die kontrollierte Hyperventilation nur im intakten Gewebe eine Vasokonstriktion verursacht (19), sind die Aussichten, mit dieser Methode em lokales Odem im Hirnstamm zu beeinflussen, gering. Die bei Hirnstammaffektionen haufig anzutreffenden Muskeltonuserhohungen und kurzdauernden Mas-senbewegungen führen bei Fehien eines generalisierten Hirnödems nicht zu bedrohlichen Steigerungen des ICP (29), so daB eine tiefe Sedierung zur ICP-Senkung nicht notwendig ist. Wegen der besseren neurologischen Beurteilbarkeit und der geringeren kardiopulmonalen Komplikation werden soiche Patienten, ausreichenden Atemantrieb vorausgesetzt, leicht his maBig sediert nach dem Konzept der ,,partiellen UnterstUtzung" beatmet.…”
Section: Infratentorielle Läsionenunclassified